Early predictors of clinical deterioration in a cohort of outpatients with COVID‐19 in southern Italy: A multicenter observational study. Issue 11 (25th July 2022) - Monari, Caterina; Pisaturo, Mariantonietta; Maggi, Paolo; Macera, Margherita; Di Caprio, Giovanni; Pisapia, Raffaella; Gentile, Valeria; Fordellone, Mario; Chiodini, Paolo; Coppola, Nicola; ,
Abstract: Data regarding early predictors of clinical deterioration in patients with infection of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is still scarce. The aim of the study is to identify early symptoms or signs that may be associated with severe coronavirus disease 2019 (COVID‐19). We conducted a multicentre prospective cohort study on a cohort of patients with COVID‐19 in home isolation from March 2020 to April 2021. We assessed longitudinal clinical data (fever, dyspnea, need for hospitalization) through video calls at three specific time points: the beginning of symptoms or the day of the first positivity of the nasopharyngeal swab for SARS‐CoV‐2‐RNA ( t 0 ), and 3 ( t 3 ) and 7 ( t 7 ) days after the onset of symptoms. We included 329 patients with COVID‐19: 182 (55.3%) males, mean age 53.4 ± 17.4 years, median Charlson comorbidity index (CCI) of 1 (0–3). Of the 329 patients enrolled, 171 (51.98%) had a mild, 81 (24.6%) a moderate, and 77 (23.4%) a severe illness; 151 (45.9%) were hospitalized. Compared to patients with mild COVID‐19, moderate and severe patients were older ( p  < 0.001) and had more comorbidities, especially hypertension ( p  < 0.001) and cardiovascular diseases ( p  = 0.01). At t 3 and t 7, we found a significant higher rate of persisting fever (≥37°C) among patients with moderate (91.4% and 58.0% at t 3 and t 7, respectively; p  < 0.001) and severe outcome (75.3% and 63.6%, respectively; p  < 0.001) compared to mild COVID‐19 outcome (27.5% and 11.7%, respectively; p  < 0.001). Factors independently associated with a more severe outcome were persisting fever at t 3 and t 7, increasing age, and CCI above 2 points. Persisting fever at t 3 and t 7 seems to be related to a more severe COVID‐19. This data may be useful to assess hospitalization criteria and optimize the use of resources in the outpatient setting.